Evolution of mutualistic behaviour between chlorella sorokiniana and saccharomyces cerevisiae within a synthetic environment. - Oosthuizen, Jennifer Rae (Stellenbosch : Stellenbosch University, 2020)
Thesis (MScAgric)--Stellenbosch University, 2020.